(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Government of India (GOI) recognizes that e-Governance, in the context of developing countries, provides an excellent open door for improving governance. These changes couldn’t just go far in improving the personal satisfaction of these sections of society, yet could really provide them more equitable access to economic opportunities than at any other time. Hence the Government of India views e-Governance as a vehicle to initiate and support reforms. The present work focuses on different e-government initiatives in India and China. This investigation targets discovering user’s perception on level of Satisfaction from e-filling Project in Indian companies. Questionnaire is administered on Company Secretaries, Chartered Accountants of different assembling and Service Sector companies of India.